Biofunctional effects of Pistacia vera addition on the quality of Simit Kebab - Ozcan, Ceyda; Capar, Tugba Dursun; Ekici, Lutfiye; Ahhmed, Abdulatef M.; Yalcin, Hasan; Yetim, Hasan (IMR PRESS, 2019)
Important changes have taken place recently in consumer's preferences towards improving their health by ingesting functional food products enriched with bioactive compounds. The aim of this study was to investigate the functionalizing effects induced by the addition of pistachio nuts (Pistacia vera (PV)) into simit kebab, a meat based product. Physicochemical properties (ph, dry matter, fat content and color values) and fatty acid composition analyses were carried out on raw simit kebab samples. Total phenolic content (TPC) and total antioxidant capacities (AC) analyses were carried out on both raw and cooked samples to determine the effects of cooking at 200 degrees C/20min. Also, the storage influences (at 4 degrees C/3 days) on the simit kebab were examined too. Significant differences in physicochemical properties were observed between the control and treated samples depending on both PV concentration and storage time (p<0.05). Color values of L* and a* in treated samples (7.5 and 10%) were significantly declined (p<0.05) in the course of storage when compared to the control samples. The TPC and AC in the treated samples showed a gradual and potential increase as the PV concentration increased. The values of TPC and DPPH inhibition ratio in 10% PV added samples were 33.60% and 53% higher than that expressed in the control samples, respectively. However, the storage period caused a reduction in both TPC and AC values of the raw samples. PV addition into simit kebab potentially increased the total polyunsaturated fatty acid (PUFA) concentration. Hence, data suggest that Pistacia vera is a good candidate of a new approach to functionalize and enhance nutritional properties of meat based products.
Keywords: Pistacia; Kebab; Pistacia vera; Antioxidans; Phenolic; Meat; food enrichment; FATTY-ACID-COMPOSITION; STORAGE STABILITY; COLOR; BEEF; ANTIOXIDANT; DISEASE; OMEGA-3-FATTY-ACIDS; PHENOLICS; SYSTEM; Chemistry; Food Science & Technology; Toxicology